Clinical and Technical Characteristics of Coronary Angiography and Percutaneous Coronary Interventions Performed before and after Transcatheter Aortic Valve Replacement with a Balloon-Expandable Valve - Alfredo Nunes Ferreira-Neto; Rishi Puri; Lluis Asmarats; Victoria Vilalta; Leonardo Guimaraes; Robert Delarochellière; Jean-Michel Paradis; Siamak Mohammadi; Eric Dumont; Josep Rodés-Cabau (Journal of Interventional Cardiology)
Objectives. To report on the feasibility and technical differences between coronary procedures performed before and after TAVR with the balloon-expandable Edwards-SAPIEN or the SAPIEN XT valves. Background. Coronary artery disease (CAD) and aortic stenosis often coexist. Transcatheter aortic valve replacement (TAVR) is emerging as a treatment for younger and lower surgical risk patients who might not present with clinically evident CAD before TAVR. The demand for performing post-TAVR coronary angiograms (CAs) and percutaneous coronary interventions (PCIs) will thus increase, posing new technical challenges. Methods. Over 1000 TAVRs were performed at the Quebec Heart and Lung Institute, of which 616 with the abovementioned valves. Of these, 28 patients had an analyzable pre- and post-TAVR CAs and 13 patients had pre- and post-TAVR PCIs performed. Procedural characteristics were gathered from all coronary procedures and subsequently compared amongst the same type of procedure performed at these two distinct time periods. Results. Neither CAs‐nor PCIs‐performed after valve implantation revealed significant differences regarding arterial access site, catheter diameter, number of diagnostic or guiding catheters used, procedural duration, fluoroscopy time, or achievement of selective coronary injection. Lesion location and classification, as well as the preference of using a drug-eluting stent, remained unchanged. During post-TAVR CA, the amount of contrast delivered and the radiation dose area product were significantly lower compared with pre-TAVR CA values. Conclusions. Performance of CA and PCI after TAVR with a balloon-expandable valve appears unaffected by its presence.